Penerapan Teknik Writing In Here And Now Berbantuan Media Audiovisual Untuk Meningkatkan Kemampuan Menulis Puisi Siswa Di Kelas X AKL 1 SMK Negeri 6 Medan - Revensyah Sihombing; Mutia Febriyana; Heppy Nadeak (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This classroom action research aims to (1) improve the ability to write poetry using the wiriting technique in here and now assisted by audiovisual media and (2) find out changes in behavior in participating in learning poetry skills using the wiriting technique in here and now assisted by audiovisual media for class X students AKL 1 SMK Negeri 6 Medan. The research method used in this classroom action research consisted of four stages, namely planning, implementing, observing, and reflecting. The research subjects were all students of class X AKL 1 at SMK Negeri 6 Medan, which consisted of 35 students. The research instrument is in the form of learning observation sheets, and student learning outcomes. Data collection techniques through observation/observation, interviews, tests and documents. The data analysis technique uses descriptive qualitative data analysis through three stages, namely reduction, analysis and conclusion of data.